The Practical Experience of Early Initiation of Breastfeeding among Primiparous Mother: A Scoping Review - Hardiyanti Fitrah Awaliyah; Sri Ratnaningsih (Women, Midwives and Midwifery, 2021)
Background: Primiparous mother has an essential role in reducing mortality and pain in newborns. One of the efforts to increase the success of Breastfeeding (ASI) is by practicing Early Initiation of Breastfeeding (IMD) by newborns to their mothers. The practice of IMD will greatly assist in the continuity of exclusive breastfeeding, so that the baby will be fulfilled up to the age of 2 years, and prevent malnourished children. Aim: To review the evidence regarding to the practical experience of Early Initiation of Breastfeeding (IMD) in primiparous mother. Method: This scoping review method used the Arksey & O'Malley framework which consisted of 5 stages, namely identifying scoping review questions with the PICO framework; identifying relevant articles by determining inclusion and exclusion criteria; searching for articles through relevant databases, namely Pubmed, Science Direct and Wiley, search for Gray Literature through the Search Engine, namely Google Scholar; Selection of articles with Prism Flow Chart which is used to describe the flow of search for articles, conduct Critical Appraisal to assess the quality of articles; undertake the charting data; compile, summarize and report results Results: Dealing with the 4 articles obtained, there were 3 articles with grade A from the RCT method, quantitative non-randomized, and qualitative. 1 grade B article with non-randomized quantitative method. Furthermore, 4 themes were obtained, namely social support, childbirth factors, the needs of primiparous mothers, and psychological factors. Conclusion: It indicated that there was a gap between the results of review articles in developed and developing countries, namely that primiparous mother in developing countries, the primiparaous mother tended to focus on the issue of support from health workers. Meanwhile the results of research in developed countries, primiparous mother focused on psychological problems.